2005
DOI: 10.2337/diacare.28.7.1547
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Lipid and Glycemic Effects of Pioglitazone and Rosiglitazone in Patients With Type 2 Diabetes and Dyslipidemia

Abstract: OBJECTIVE -Published reports suggest that pioglitazone and rosiglitazone have different effects on lipids in patients with type 2 diabetes. However, these previous studies were either retrospective chart reviews or clinical trials not rigorously controlled for concomitant glucoseand lipid-lowering therapies. This study examines the lipid and glycemic effects of pioglitazone and rosiglitazone.RESEARCH DESIGN AND METHODS -We enrolled subjects with a diagnosis of type 2 diabetes (treated with diet alone or oral m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
568
6
11

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 762 publications
(625 citation statements)
references
References 49 publications
40
568
6
11
Order By: Relevance
“…In fact, it has been shown that RSG administration to diabetic patients decreases the circulating levels of glycated hemoglobin. 54 The decrease of peritoneal AGEs in PD fluid instilled mice fits well with the observed reduction of MMT, fibrosis and angiogenesis, and with the preservation of the mesothelium in vivo. Furthermore, the better preservation of the mesothelium may also be explained by a direct effect of RSG on mesothelial cell survival, as witnessed in vitro by analyzing apoptosis.…”
Section: Discussionsupporting
confidence: 55%
“…In fact, it has been shown that RSG administration to diabetic patients decreases the circulating levels of glycated hemoglobin. 54 The decrease of peritoneal AGEs in PD fluid instilled mice fits well with the observed reduction of MMT, fibrosis and angiogenesis, and with the preservation of the mesothelium in vivo. Furthermore, the better preservation of the mesothelium may also be explained by a direct effect of RSG on mesothelial cell survival, as witnessed in vitro by analyzing apoptosis.…”
Section: Discussionsupporting
confidence: 55%
“…These results are in accordance with the known hypolipidaemic effects of n-3 LC-PUFA [1] and rosiglitazone [25] in mice. Interest- ingly, in humans, only pioglitazone but not rosiglitazone exerted a hypolipidaemic effect [19], documenting that the hypolipidaemic effect of TZDs may be dissociated from their effect on insulin sensitivity [25]. The lowering of NEFA levels in mice subjected to various treatments could reflect several mechanisms, including adipose tissue lipolysis, re-esterification of NEFA in liver and adipose tissue, and stimulation of lipid oxidation in liver [14] and other organs [10] by n-3 LC-PUFA, as well as by TZDs [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PPAR-γ ligands [19] such as thiazolidinediones (TZDs) are the preferred therapeutic agents for insulin resistance in type 2 diabetic patients. However, TZDs like rosiglitazone and pioglitazone are also associated with unwanted side effects, such as oedema and weight gain [20], possible risk of heart failure [21] and bone loss [22].…”
Section: Introductionmentioning
confidence: 99%
“…There is an increase in adiposity, largely subcutaneous, with some reduction in visceral fat shown in some studies. The TZDs either have a beneficial (pioglitazone) or neutral (rosiglitazone) effect on atherogenic lipid profiles [63,64]. Several meta-analyses have suggested a 30-40% relative increase in risk for myocardial infarction [65,66] with rosiglitazone.…”
Section: Medicationsmentioning
confidence: 99%